Estimates of the government of Borno State of Nigeria. ([Maiduguri], [publisher not identified], 1977)
The budget for the year 1976/77 of Borno State
aia 12/02/2019
Loans
Keywords: Budget; Budget; Expenditures, Public; Borno State (Nigeria); Nigeria